Perception of the Aesthetics of a Smile in Patients Post Using Orthodontic Treatment Based on Characteristics - Lina Hadi; Valerin Angelina; Zulfan Muttaqin; Berliana Sihombing (Archives of The Medicine and Case Reports, 2021)
Aesthetics is a philosophy of the concept of beauty which is the reason people take orthodontic treatment. One of the factors that influence aesthetics is a smile. Apart from personal experiences and social environment, the patient's perception of the aesthetics of the smile after orthodontic treatment can be influenced by characteristics. This study aims to determine the perception of smile aesthetics in post-orthodontic patients based on characteristics. This type of research is descriptive-analytic with a cross-sectional design. The study population was patients who were recorded in medical records at the practice of drg. Josep Ginting, Sp. Ort in Pontianak, West Kalimantan Province with a sample size of 30 people. Collecting data by distributing questionnaires containing nine aesthetic indicators of smiles through the WhatsApp application. Data were analyzed using the Mann-Whitney test. Based on the results of the study, it was seen that there were differences in the aesthetic perceptions of respondents' smiles based on age (p = 0.017), gender (p = 0.004), and education (p = 0.015). The conclusion of this study is that there are differences in patient perceptions of an aesthetic smile after orthodontic treatment based on the characteristics in the practice of drg. Josep Ginting, drg, Sp. Ort in Pontianak, West Kalimantan.